2011
DOI: 10.1159/000324218
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease and Associated Risk Factors, and Risk of End-Stage Renal Disease: Data from the PREVADIAB Study

Abstract: Background/Aims: Chronic kidney disease (CKD) is a growing public health problem. However, data on risk factors and prevalence of CKD exist only in a small number of countries. Portugal has the highest incidence of end-stage renal disease (ESRD) among European countries, but there are huge disparities among countries. Whether these disparities reflect differences in risk factors, prevalence of CKD or other factors is currently unknown. Methods: We analyzed data from a nationally representative sample of 5,167 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
1
41
0
3
Order By: Relevance
“…Another national study [15], carried out between 2006 and 2007, with different selection criteria and including an older population (mean age of 58.1 years), observed crude MetS prevalence rates of 28.4%, 65.5% and 69.4%, respectively, discretely higher than those in the present study. The PREVADIAB study conducted from 2008 to 2009 showed a crude prevalence of 41.5% by IDF criteria [14]. Nevertheless, the national prevalence of MetS is higher than in some European countries and the USA [8].…”
Section: Discussionmentioning
confidence: 99%
“…Another national study [15], carried out between 2006 and 2007, with different selection criteria and including an older population (mean age of 58.1 years), observed crude MetS prevalence rates of 28.4%, 65.5% and 69.4%, respectively, discretely higher than those in the present study. The PREVADIAB study conducted from 2008 to 2009 showed a crude prevalence of 41.5% by IDF criteria [14]. Nevertheless, the national prevalence of MetS is higher than in some European countries and the USA [8].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients with chronic kidney disease (CKD) is rising to epidemic proportions [1]. In 2008, the median prevalence of CKD was 7% in persons aged 30 years or older.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Although additional risks for the progression of CKD such as physical inactivity, smoking and obesity are underestimated in Jordanian patients, they are well appreciated in other populations. 2,3 Obesity is highly associated with release of lipolysis products into the systematic circulation in addition to the inflammatory mediators such as cytokines. 2 These mechanism may interfere with the engagement of the individual in a healthy lifestyles.…”
Section: Introductionmentioning
confidence: 99%